A Contribution of Picture Communication Boards on expressive Language Skills of Learners with Hearing Impairment - Sharon, Onditi; Adhiambo, Oronge Evernate; Alfred, Otara (African Journal of Education,Science and Technology (AJEST), 2024)
The most effective tool for human advancement is communication, encompassing the expressive aspect, which is crucial in various life aspects, demonstrating its importance in communication skills. Picture communication boards include sheets of symbolic presentation, letters, and real-life pictures that a learner may point to communicate with others. Guided by Albert Bandura’s Social Learning Theory, the objective of the study was to determine the contribution of picture communication boards on the expressive language skills of learners with hearing impairment using a mixed-method approach within a descriptive survey design. The target population comprised 73 learners, 46 teachers, 7 headteachers, and 5 Educational Assessment and Resource Centre officers (EARCs), selected purposely. Quantitative data from the main respondents were collected through questionnaires and observation checklists. Simultaneously, interview guides were utilized to gather qualitative data from key informants. Quantitative data were analyzed descriptively based on means, frequencies, and standard deviation, and inferentially based on Pearson Correlation, presented in tables. Qualitative data were presented in narratives after thematic analysis. The study concludes that the utilization of communication boards enhances the expressive language skills of learners with hearing impairment through the use of pictures, charts, relevant books, and tables. The study recommends that the Ministry of Education, through the Directorate of Special Needs Education, should upscale the use of communication boards as a teaching aid for learners with hearing impairment.